GE_GERICHTE C/26524/2014 vom 28. Mai 2019 - GE Cour de justice (2019)
ACTION EN RESPONSABILITÉ;AVOCAT;ACTION EN DIVORCE;IMMEUBLE;RÉGIME MATRIMONIAL | CO.97.al1; CO.398.al2; CO.44.al1; aCC.140; CL.22.ch1